Teaching Observation Skills: A Survey of CSD Program Practices. - Hall, Nancy (Contemporary Issues in Communication Science & Disorders)
Purpose: The purposes of this study were to explore pedagogical perspectives on the role of observation in medical and allied health professions and to present the results of a survey on how communication sciences and disorders (CSD) academic programs provide clinical observation training and experience in speech-language pathology. Method: Directors for undergraduate-only programs with membership in the Council on Academic Programs in Communication Sciences and Disorders and program directors for American Speech-Language-Hearing Association's Council for Clinical Certification-accredited programs were surveyed as to the structure and nature of clinical observation experiences for their students. Results: The data indicated that most programs provide opportunities for clinical observation in undergraduate classes or via recording along with observations of real-time sessions in both on- and off-campus facilities. Although a majority of programs (74%) require students to complete assignments associated with the observations (typically written reports), only 64% of programs provide specific training in observation skills, and even fewer (57%) have explicit objectives outlined for the observation experiences. Conclusion: Although observation is considered an important component of the clinical process, little substantive work is available in the CSD literature to guide academic programs and students. The results of this study are discussed with respect to how CSD programs could make use of pedagogical trends in the training of observation skills in other health care disciplines, particularly medicine, to enhance these experiences for their students. Caveats regarding the present study and considerations for the future are offered.